Does luck make people more optimistic and patient? Lessons from an experiment with students and rural subjects in Malawi - Stein Terje Holden; Sarah Tione; Mesfin Tilahun; Samson Katengeza (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
We investigate how random luck in repeated variants of the risky investment game of Gneezy, Leonard, and List (2009); Gneezy and Potters (1997) influences risk-taking and discounting behavior in future risky prospects with probabilistic payouts one week, six, 12, and 24 months into the future. We test non-parametrically whether luck enhances risk-taking and patience (reduces the discount rate) in risky prospects with delayed payouts. To investigate whether luck influences probability weighting (w(p) function), we estimate structural models with two-parameter Prelec probability weighting functions to decompose risk-taking in prospects with potential payouts six and 12 months into the future. We find that luck results in more optimistic (reduces the Prelec Ø parameter) and less non-linear (inverse-S-shaped) (increases the Prelec » parameter) w(p) function. We assess this for two samples from Malawi: one is a random sample of university students (n=721), and the other is a random sample (n=835) of rural subjects with limited education. The students were found to be more patient but had similar probability weighting functions.
hdl:11250/3142185
Keywords: C91; C93; D81; D84; D91; 330; Luck; Discounting; Risk-taking; Probability weighting